Dynamic Body Composition Adaptations in Young Athletes (15–17 Years Old): A Two-Year Follow-Up Using Professional Bioelectrical Impedance Monitoring. - Moussa, Boutahra; Salim, Kedjadja; Mansouri, Samir; Salim, Mekhancha; Mokhtar, Aknouche (Journal of Neonatal Surgery, 2026)
Background: Monitoring body composition in youth athletes is essential for understanding growth, training-related adaptations, and health trajectories during adolescence. Professional bioelectrical impedance analysis (BIA) provides a practical and reliable method to evaluate these changes longitudinally. Objective: To examine two-year changes in skeletal muscle mass, fat mass, bone mass, and body mass index (BMI) in young amateur football players using repeated BIA assessments. Methods: Twenty male regional-level football players (mean age: 15.9 years; height: 169 cm; weight: 52.82 kg) were followed across two competitive seasons (2023–2024 and 2024–2025). Body composition was measured at four standardized time points (start and end of each season) using a professional BIA system (Tanita PRO 780). The training regimen consisted of four sessions per week over 26-week seasons (~170 hours per season). Analyses included repeated measures comparisons, Wilcoxon tests, and effect size calculations (Cohen’s d). Results: Muscle mass increased significantly over the two years (+5.66 kg, d = 2.05, +9.17%). Bone mass showed a substantial increase (+0.40 kg, d = 2.21, +17.39%). Fat mass remained stable over time (–0.01 kg, d = 0.01, 0.13%). BMI increased moderately (+1.24 kg/m², d = 0.97, +6.84%). Early seasonal fluctuations were not cumulative, while long-term improvements in lean and bone tissue were pronounced. Conclusion: Two consecutive seasons of structured football training induced significant gains in muscle and bone mass, maintained stable fat mass, and moderately increased BMI in young athletes. Professional BIA is a valuable tool for monitoring growth and physiological development in adolescent sports contexts